Radiative association of Ti and O atoms - Andreazza, C. M. [UNESP]; de Almeida, A. A.; Vichietti, R. M.; Ceccatto, D. T. [UNESP] (Oxford University Press, 2012)
Rate coefficients for the radiative association of titanium and oxygen atoms to form the titanium monoxide (TiO) molecule are estimated. The radiative association of Ti(F-3) and O(P-3) atoms is dominated by an approach along the C-3 Delta potential energy curve, accompanied by spontaneous emission into the X-3 Delta ground state of TiO. For temperatures ranging from 300-14 000 K, the total rate coefficients are found to vary from 4.76 x 10(-17) to 9.96 x 10(-17) cm(3) s(-1), respectively.
Keywords: atomic data; atomic processes; circumstellar matter; ISM: molecules